The Influence of Job Training, Financial Compensation, and Career Development on Employee Performance PT Ungaran Sari Garment Ungaran Branch - Annisa Himatul Maulidya; Ninik Dwi Atmini; Adji Seputro (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
PT Ungaran Sari Garment is one of the Largest Export Oriented Apparel Company in Indonesia, operating world-class factories in various locations in Java supported by 11,000 skilled and professional workers. Ungaran Sari Garments' production capacity can handle 1.7 million dozen garments per year and still with great potential for expansion. In 2022 to 2024 experienced an increase and decrease in Actual Performance Production. Production Performance data at PT Ungaran Sari Garment for the last 3 years has experienced, indicates that there is a decrease in employee performance at PT Ungaran Sari Garment.